Manisha Koirala’s Celebrity Persona: A Case Study (American Journal of Arts and Human Science, 2024)
This qualitative study delves into the life and career of actress Manisha Koirala, particularly focusing on authenticity, philanthropy and activism, ageing, and scandal. The study explores Manisha Koirala’s public persona, her active engagement in philanthropic activities, her perceived authenticity, and her career in the film industry. Furthermore, this research explores the challenges and difficulties posed by ageing and how she is dealing with them in her life and career. It also studies how she reacts to the scandal in the media and how it shapes her image in the public eye after the scandal. The research used case study as the methodology to study several aspects of Manisha Koirala’s life and career by gathering information from various sources, such as news stories, media reports, her public statements, and interviews. The findings of this study are that through her acting and activities, she is an authentic celebrity and takes the scandal news positively without reacting or embracing the ageing process.